Molecular docking approach to identify Bcl-xL inhibitory effect of sesquiterpene coumarins of Ferula species - Fadıl Kaan Kuran; Ebru Didem Kuran; Mahmut Miski (İstanbul Journal of Pharmacy)
Background and Aims: Due to the high mortality and morbidity rates associated with cancer, it is crucial to advance research in this area to develop new and effective agents. Natural product chemistry plays a crucial role in identifying potential lead molecules for the treatment of various cancers. Recently, several studies have demonstrated the selective and potent cytotoxic activity of sesquiterpene coumarins isolated from Ferula species against various cancer cell lines. In this study, we aimed to utilize in silico molecular docking studies to demonstrate the potential of sesquiterpene coumarins as inhibitors of Bcl xL. For this purpose, 35 sesquiterpene coumarins were collected based on previous studies.Methods: Molecular docking studies were conducted to examine the interactions of cytotoxic sesquiter pene coumarins with the active site of the Bcl-xL enzyme, using advanced computational techniques. Additionally, ADME (Absorption, Distribution, Metabolism, and Excretion) studies were performed to predict the pharmacokinetic properties and drug-likeness of sesquiterpene coumarins, ensuring their potential as viable therapeutic agents.Results: As a result of this study, straight-chain sesquiterpene coumarin-derived compounds were more effectively positioned within the active site of the Bcl-xL enzyme and formed hydrogen bonds with amino acids. ADME analysis revealed favourable pharmacokinetic profiles, supporting their potential use in drug development.Conclusion: These findings revealed promising Bcl-xL inhibitory activities of umbelliprene-type sesquiter pene derivatives, which might be a starting point for further structural optimisation to acquire novel compounds exhibiting more potent Bcl-xL inhibitory activity, paving the way for new therapeutic approaches in cancer treatment.